Lamproderma ovoideum - Krivomaz, T. I.; Michaud, A.; Minter, D. W. (CABI, 2010)
Diagnostic features. Nivicolous species of Lamproderma have dark, often blackish, metallic, iridescent, shiny, separate, globose or nearly globose and stipitate to sessile sporocarps. Lamproderma ovoideum, perhaps the most common nivicolous member of this genus, has ovoid sporocarps and may be distinguished by spore size and ornamentation from other nivicolous species of Lamproderma with similar sporocarps.
Keywords: myxomycetes; міксоміцети; Lamproderma ovoideum